From Watwat to Betel Nut: How are Cordillerans portrayed in local memes? - C. Amparo, Iveeh; E. Luban , Lory Jane; B. Quinto, Joseph (Asia Social Issues, 2025)
The growth of social media has enabled users to quickly generate memes on digital platforms. Even though users design memes to express ideas and identities, researchers need to give more attention to the evident gap in how Cordillerans are portrayed through memes on social media. Therefore, this research aims to fill this gap by specifically examining how the Taga Lakandula Facebook Page portrays Cordillerans through memes. Using netnography, the researchers had to immerse themselves in the virtual world for two months, repeatedly reading and analyzing the memes, which included constant correspondence with the person in charge of the Facebook page. The researchers adopted stages of content analysis and sought help from an external expert in the field who reviewed the memes vis-à-vis the findings to see if they were plausible and accurate. The findings revealed that the memes portray Cordillerans as drunkards, betel nut users, proud, gamblers, shy, ‘watwat’ eaters, and observants. Overall, this research adds to the literature on Cordilleran portrayals and Internet memes and recommends future research trajectories.